Growth hormone, insulin and aging: The benefits of endocrine defects - Bartke, Andrzej (2010)
Longevity of mice can be increased by spontaneous or experimentally induced mutations that interfere with the biosynthesis or actions of growth hormone (GH), insulin-like growth factor 1 (IGF-1), or insulin in the adipose tissue. The effects of GH resistance and deficiency of GH (along with thyrotropin and prolactin) on aging and lifespan are the most pronounced and best established of these mutations. Potential mechanisms linking these endocrine deficits with delayed aging and extended longevity include increased stress resistance, alterations in insulin and mammalian target of rapamycin (mTOR) signaling and metabolic adjustments. Physiological relationships deduced from the extreme phenotypes of long-lived mouse mutants appear to apply broadly, encompassing genetically normal (“wild-type”) mice and other mammalian species. The role of GH in the control of human aging continues to be hotly debated, but recent data indicate that reduced somatotropic signaling provides protection from cancer and other age-related diseases and may promote old age survival.